Determination of 137Cs Elimination from Solution By Tasikmalaya Bentonite and Belitung Quartz Sand As Barrier Material Candidate on the Near Surface Disposal Facility - Budi Setiawan; Heru Sriwahyuni (Syarif Hidayatullah State Islamic University, 2018)
Batch technique experiment was applied to measure the elimination of 137Cs from solution using bentonite from Tasikmalaya and quartz sand from Belitung. Bentonite material was used as barrier system surrounding on a near surface disposal facility, and quartz sand as backfill material. The distribution coefficient (Kd) of 137Cs on bentonite and quartz sand samples have been measured. Contact time, variation of Na and Cs ion concentrations in solution were applied as the experiment parameters. The Kd values of 137Cs on the samples were 1700 and 3200 ml/g for bentonite and 17 and 37 ml/g for quartz sand samples, respectively. The Na and Cs concentrations in solution affected the Kd values of 137Cs on samples. Isotherm sorption result shown that the interaction of 137Cs onto solid samples was approached with Freundlich model. The data obtained from the experiments and then could be used for radionuclides migration assessment models of disposal facility in the future.DOI:http://dx.doi.org/10.15408/jkv.v4i1.7325